Hyperpolarized relaxometry based nuclear T(1) noise spectroscopy in diamond - Ajoy, A. (Nat Commun, 2019)
The origins of spin lifetimes in quantum systems is a matter of importance in several areas of quantum information. Spectrally mapping spin relaxation processes provides insight into their origin and motivates methods to mitigate them. In this paper, we map nuclear relaxation in a prototypical system of [Formula: see text] nuclei in diamond coupled to Nitrogen Vacancy (NV) centers over a wide field range (1 mT-7 T). Nuclear hyperpolarization through optically pumped NV electrons allows signal measurement savings exceeding million-fold over conventional methods. Through a systematic study with varying substitutional electron (P1 center) and [Formula: see text] concentrations, we identify the operational relaxation channels for the nuclei at different fields as well as the dominant role played by [Formula: see text] coupling to the interacting P1 electronic spin bath. These results motivate quantum control techniques for dissipation engineering to boost spin lifetimes in diamond, with applications including engineered quantum memories and hyperpolarized [Formula: see text] imaging.